Mechanistic Insight Into the AuCN Catalyzed Annulation Reaction of Salicylaldehyde and Aryl Acetylene: Cyanide Ion Promoted Umpolung Hydroacylation/Intramolecular Oxa-Michael Addition Mechanism - Yang, Manyi; Wang, Guoqiang; Zou, Jingxiang; Li, Shuhua (Frontiers in Chemistry, 2019)
Abstract: The detailed mechanism of the AuCN-catalyzed annulation of salicylaldehyde (SA) and phenyl acetylene leading to isoflavanone-type complexes has been investigated via density functional theory (DFT) calculations. Reaction pathways and possible stationary points are obtained with the combined molecular dynamics and coordinate driving (MD/CD) method. Our calculations reveal that the cyanide ion promoted umpolung hydroacylation/intramolecular oxa-Michael addition mechanism is more favorable than the Au(I)/Au(III) redox mechanism proposed previously. In the umpolung mechanism, the hydroxyl of SA is found to strongly stabilize the cyanide ion involved intermediates and transition states via hydrogen bond interaction, while the Au(I) ion always acts as a counter cation. The overall reaction is exergonic by 41.8 kcal/mol. The hydroacylation of phenyl acetylene is the rate-determining step and responsible for the regioselectivity with a free energy barrier of 27.3 kcal/mol. These calculated results are in qualitative accord with the experimental findings.